Early degradation factors of solar 33 kV grid connected power plant, a comparative study - Elhassene, Issa Cheikh; El Heiba, Bamba; Taha, Mohammed Qasim; Mahmoud, Teyeb Med; Aoulmi, Zoubir; Youm, Issakha; Mahmoud, Abdelkader (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
This paper identifies and analyses early degradation mechanisms observed in photovoltaic (PV) modules of power plants over 7 years of operation on the coast power grid in Mauritania. Performance degradation takes place due to several reasons such as material degradation following dust accumulation, high temperature, and humidity. Also, mismatch of electric power parameters such as increasing loads above projected values of the plant. Therefore, this paper analyses and studies the degradation in four phases. First, the visual inspection detects the degradation of materials and defects such as the presence of dust, cracks, browning (discoloration), and connection corrosion. The second phase proposes a mathematical model to calculate the early degradation rate (DR) of different components, such as short circuit current (Isc), open circuit voltage (VOC), the maximum yield power (Pmax), and the fill factor (FF) of the PV module. The third phase is a MATLAB modeling of the measured real-time data of the operating PV system to test Power versus voltage curves (with and without degradation) to examine the presence of failure of PV modules. Finally, compare the evolution of real-time production data for three measured years (2015, 2016, and 2017) with the simulation curves of this study.